Predictive value of prealbumin combined with neutrophil-to-lymphocyte ratio in early postoperative complications of gastric cancer - GUO Maosen, LI Hu, GAO Fei, HAN Bin (Zhongguo linchuang yanjiu)
"Objective To investigate the predictive value of prealbumin combined with neutrophil-to-lymphocyte ratio (NLR) for early postoperative complications (EPC) in patients undergoing radical gastrectomy. Methods A retrospective case-control study was performed. The clinical data of 255 gastric cancer patients who underwent radical gastrectomy and D2 lymph node dissection in the Department of General Surgery, the Second Affiliated Hospital of Zhengzhou University from January 2019 to March 2023 were collected and divided into EPC group (n=63) and nonEPC group (n=92), and the differences of prealbumin and NLR between the two groups at different time points were compared, and the receiver operator characteristic (ROC) curve was plotted to analyze the predictive value of prealbumin, NLR and their combination on the development of EPC in gastric cancer patients after surgery. Multivariate logistic regression was used to analyze the independent risk factors for the EPC in gastric cancer patients. Results The prealbumin level in the EPC group was lower than that in the non-EPC group on postoperative day 1 and 3 (P<0.01); NLR was higher than that in the nonEPC group on postoperative day 3 (P<0.01). ROC curve showed that the optimal cut-off value for prealbumin to predict EPC on postoperative day 1 was 209 mg/L, with an area under curve (AUC) of 0.645 (95%CI0.559-0.731, P<0.015), a sensitivity of 88.1% and a specificity of 44.5%; the optimal cut-off value for NLR on postoperative day 3 to predict EPC was 5.89, with an AUC of 0.753 (95%CI 0.670-0.835， P<0.01), a sensitivity of 69.0% and a specificity of 77.3%; the AUC predicted jointly by them was 0.818 (95%CI 0.742-0.894,P<0.01), with a sensitivity of 76.2% and a specificity of 78.9%, and the AUC of the joint prediction was the largest. The results of multivariate analysis showed that the type of surgical incision being open, the duration of surgery ≥ 270 min, decreased prealbumin on postoperative day 1 and increased NLR on postoperative day 3 were independent risk factors for predicting EPC in gastric cancer (P<0.05). Conclusion Prealbumin on postoperative day 1 combined with NLR on postoperative day 3 has a good predictive value for the development of early complications after radical gastrectomy."